Perbandingan Metode K-Nearest Neighbor Dan Decision Tree Pada Sistem Rekomendasi Laptop - Muhammad Izdihar Alwin; Firza Prima Aditiawan; Muhammad Muharrom Al Haromainy (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
Nowadays, many people need a laptop to serve their daily needs such as work, study or entertainment. However, not everyone knows the indicators in the selection of laptop products according to taste and criteria for laptop needs with the variety of laptop specifications available on the market. To overcome these problems, a laptop recommendation system has been developed. This system will help consumers choose a laptop that suits their needs by recommending various laptop options based on the preferences and features that users enter. In this research, K-Nearest Neighbor and Decision Tree algorithms are used to see the performance in providing recommendations.